Odpowiedź :
a) x-2x+1-2x=6x-8
x-2x-2x-6x=-8-1
-9x=-9
x=1
b) 3x-6-x+3=-5x+4
3x-x+5x=4+6-3
7x=7
x=1
e) 2x-3x+4=-12x+4
2x-3x+12x=4-4
11x=0
Równanie sprzeczne
g) -5x-4+x-1-1+x=0
-5x+x+x=4+1+1
-3x=6
x=-2
x-2x-2x-6x=-8-1
-9x=-9
x=1
b) 3x-6-x+3=-5x+4
3x-x+5x=4+6-3
7x=7
x=1
e) 2x-3x+4=-12x+4
2x-3x+12x=4-4
11x=0
Równanie sprzeczne
g) -5x-4+x-1-1+x=0
-5x+x+x=4+1+1
-3x=6
x=-2
Odpowiedź:
a) x - (2x - 1) - 2x = 2(3x - 4)
x - 2x + 1 - 2x = 6x - 8
x - 2x - 2x - 6x = - 8 - 1
- 9x = - 9 /: (-9)
x = 1
b)
3(x - 2) - (x - 3) = - (5x - 4)
3x - 6 - x + 3 = - 5x + 4
3x - x + 5x = 4 + 6 - 3
7x = 7 / : 7
x = 1
e)
2x + (- 3x + 4) = - 4 (3x - 1)
2x - 3x + 4 = - 12x + 4
2x - 3x + 12x = 4 - 4
11x = 0 / :11
x = 0
g)
-(5x + 4) +(x - 1) - (1 - x) = 0
- 5x - 4 + x - 1 - 1 + x = 0
- 5x + x + x = 4 + 1 + 1
- 3x = 6 / : (- 3)
x = - 2
Szczegółowe wyjaśnienie: